Co-gasification of black liquor and pyrolysis oil at high temperature: Part 1. Fate of alkali elements. (15th August 2017) - Bach-Oller, Albert; Kirtania, Kawnish; Furusjö, Erik; Umeki, Kentaro
Highlights: Blends of black liquor (BL) and pyrolysis oil (PO) were gasified in a drop tube. Equilibrium modelling qualitatively captured the fate of alkali species. Experimental vaporization of alkali exceeded the prediction by equilibrium. Diluting the alkali by blending PO in BL did not lead to alkali depletion in the char. Abstract: The catalytic activity of alkali compounds in black liquor (BL) enables gasification at low temperatures with high carbon conversion and low tar and soot formation. The efficiency and flexibility of the BL gasification process may be improved by mixing BL with fuels with higher energy content such as pyrolysis oil (PO). The fate of alkali elements in blends of BL and PO was investigated, paying special attention to the amount of alkali remaining in the particles after experiments at high temperatures. Experiments were conducted in a drop tube furnace under different environments (5% and 0% vol. CO2 balanced with N2 ), varying temperature (800–1400 °C), particle size (90–200 µm, 500–630 µm) and blending ratio (0%, 20% and 40% of pyrolysis oil in black liquor). Thermodynamic analysis of the experimental cases was also performed. The thermodynamic results qualitatively agreed with experimental measurements but in absolute values equilibrium under predicted alkali release. Alkali release to the gas phase was more severe under inert conditions than in the presence of CO2, but also in 5% CO2 most of the alkali was found in the gas phase at T = 1200 °C and above. However, the concentration of alkali in the gasification residue remained above 30% wt. and was insensitive to temperature variations and the amount of PO in the blend. Thermodynamic analysis and experimental mass balances indicated that elemental alkali strongly interacted with the reactor's walls (Al2 O3 ) by forming alkali aluminates. The experience indicated that adding PO into BL does not lead to alkali depletion during high temperature gasification.